Suggestions for the diagnosis and elimination of hepatitis E virus in pigs used for xenotransplantation. (7th May 2013) - Busby, Stacey‐Ann; Crossan, Claire; Godwin, Jon; Petersen, Bjoern; Galli, Cesare; Cozzi, Emanuele; Takeuchi, Yasu; Scobie, Linda
Abstract The hepatitis E virus (HEV) is considered a zoonotic pathogen. In xenotransplantation, given the high prevalence of HEV infection in pigs, the risk of zoonotic transmission from a porcine source is considered high. Currently no clear data are available on how to diagnose and eliminate HEV in herds used for medical purposes and the importance of viral infection at the stage of harvest. In this study, several groups of animals currently used for medical purposes were found RNA positive in both serum and faeces for HEV genotype 3. In addition, viraemia was found in animals up to 3.6 yr of age, which is much longer than originally expected. Herd transmission rates appeared to be significantly lower in animals kept under minimal barrier conditions, compared with those observed for commercial animals, and as expected, segregation of animals at an early age prevented spread of infection. This study makes suggestions to ensure appropriate detection and eradication of HEV from a donor herd to be used for xenotransplantation purposes.